A study on employee's perception on reward system offered at National Treasury Department of Malaysia / Marlina Syamsuri - Syamsuri, Marlina (2009)
This research was done based on the starting point where it is essential for every organisation to have a good reward system structure. In an organisation, a good reward system could ensure the organisation is being fair towards all its employees. Although it's hard to evaluate employee's level of satisfaction, information on individual's perception towards such system in an organisation could be generated for that reason.